4-H Florida-Friendly Landscaping™ Workbook - John Pipoly; Angelina Toomey; Sarah Hensley; Esen Momol; Jennifer W. Marvin; Kelly Perez (EDIS, 2021)
Florida-Friendly LandscapingTM (FFL) protects natural resources through water conservation, waste and nonpoint source pollution reduction, erosion prevention, and creation of wildlife-sustaining habitats by implementing science-based landscaping practices. 4-H Florida-Friendly LandscapingTM Curriculum fosters environmental stewardship among youth and allows them to engage in conserving water, soil, and vegetation resources from an early age.